Izmjene zakonskih mjera u Europi glede onečišćenja okoliša od motornih vozila - Lulić, Zoran (Promet - Traffic&Transportation, 2012)
This paper deals with some new things in legal provisions on environmental pollution from motor vehicles as implemented in the EC member states. Besides discussing some novelties, the paper deals with the existing situation and makes a review and gives a concise description of tests to be met by each new model of motor vehicles to be granted a certificate for sale on the European market.